EMF-Aware Probabilistic Shaping Design for Hardware-Distorted Communication Systems - Javed, Sidrah; Elzanaty, Ahmed; Amin, Osama; Alouini, Mohamed-Slim; Shihada, Basem (Frontiers in Communications and Networks, 2022)
Fifth-generation cellular network requires dense installation of radio base stations to support ever-increasing demands of high data-rates and coverage. The ongoing deployment has triggered some health concerns among community. To address this uncertainty, we propose an EMF-aware probabilistic shaping design for hardware distorted communication systems. The proposed scheme aims to minimize human exposure to radio frequency radiations while achieving the target throughput using probabilistic shaping. The joint optimization of the transmission power and non-uniform symbol probabilities is a non-convex optimization problem. Therefore, we employ alternate optimization and successive convex approximation to solve the subsequent problems. Our findings reveal a significant reduction in the users' exposure to EMF while achieving the requisite quality-of-service with the help of probabilistic shaping in a hardware distorted communication system.